2020
DOI: 10.1002/etc.4891
|View full text |Cite
|
Sign up to set email alerts
|

Fate and Fathead Minnow Embryotoxicity of Weathering Crude Oil in a Pilot‐Scale Spill Tank

Abstract: For several years now, the Natural Resources Canada research facility at CanmetENERGY Devon (AB, Canada) has been performing experiments in a pilot-scale spill tank using 1200 L of river water to examine the physical and chemical behaviors of various crude oil/water mixtures under varying water temperature regimes. Because oil toxicity can be modulated by weathering of the petroleum products, the present study aimed to assess changes in fish embryotoxicity to mixed sweet blend crude oil as it weathered at air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…As expected, PACs and VOCs rapidly disappeared from the water column of the experimental chambers. Several studies have also observed this rapid disappearance (e.g., Lara-Jacobo et al, 2021;Redman and Parkerton, 2015;Robidoux et al, 2018) due to the hydrocarbon volatilization, sedimentation, or adhesion to the test chamber glass. Volatilization concerns the very light fractions of the hydrocarbons (Fingas, 2013;NAS, 2016).…”
Section: Chemical Composition Of the Wafsmentioning
confidence: 94%
See 2 more Smart Citations
“…As expected, PACs and VOCs rapidly disappeared from the water column of the experimental chambers. Several studies have also observed this rapid disappearance (e.g., Lara-Jacobo et al, 2021;Redman and Parkerton, 2015;Robidoux et al, 2018) due to the hydrocarbon volatilization, sedimentation, or adhesion to the test chamber glass. Volatilization concerns the very light fractions of the hydrocarbons (Fingas, 2013;NAS, 2016).…”
Section: Chemical Composition Of the Wafsmentioning
confidence: 94%
“…Everitt et al (2020) when exposing the epibenthic amphipod Hyalella azteca to a water-soluble fraction (WSF, similar to WAF but excluding droplets or particulate oil) of a weathered diluted bitumen containing 1.08 μg/L total PAHs did not observe lethality. Overall, few studies have compared the toxicity of dissolved compounds in diluted bitumen with conventional oil to aquatic organisms (Berube et al, 2021;Lara-Jacobo et al, 2021) and, to our knowledge, there are none on benthic invertebrates. Most current literature on the toxicity of diluted bitumen on aquatic species is on fish (Wallace et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the meso-scale spill tanks at the CanmetE-NERGY Devon facility has been described in previous studies (Lara-Jacobo et al, 2020). In short, the stainless-steel spill tank (Figure 1) is 3 × 1 × 1.5 m in length × width × height with one narrow end of the tank built at an incline to simulate a shoreline situation.…”
Section: Spill Testsmentioning
confidence: 99%
“…The particle size (Supporting Information, Figure S1) and mineral distribution (Supporting Information, Table S1) of the river sediment were determined using previously established protocols prior to being used in the spill tests (Lara-Jacobo et al, 2020). Both the oil dissolved and/or dispersed in the water column and the oil associated with bottom sediment were quantified using a dichloromethane extraction method.…”
Section: Water Oil and Sediment Analysismentioning
confidence: 99%